A Multimodal Instructional Design Model: Integrating Infographics and Interactive Videos in Arabic Language Learning - Menik Mahmudah; Hanik Mahliatussikah; Muhamad Solehudin; Masnun; Nur Aunie Batrisya (Postgraduate of IAIN Metro Lampung Indonesia, 2026)
Arabic language instruction in secondary Islamic education has traditionally relied on text-based explanation and memorization, which often fails to address learners’ cognitive diversity and engagement in digital learning environments. This study aims to develop and evaluate a multimodal instructional design model integrating infographics and interactive videos to enhance Arabic language learning, particularly vocabulary and grammar mastery. Grounded in Mayer’s Cognitive Theory of Multimedia Learning and structured through the ADDIE framework, the study employed an exploratory sequential mixed-methods approach. Data was collected through pre- and post-tests, classroom observations, questionnaires, and semi-structured interviews involving 60 Madrasah ‘Aliyah students divided into experimental and control groups. The multimodal materials were developed using Canva, Powtoon, and H5P and implemented over six weeks. Quantitative results showed a statistically significant improvement in the experimental group’s vocabulary and grammar achievement (p < .05), while qualitative findings indicated increased motivation, engagement, and conceptual understanding. The novelty of this study lies in its empirically validated multimodal instructional design model that systematically integrates visual and interactive elements within Arabic language pedagogy. The findings suggest that sustained teacher training in digital pedagogy is essential to support the effective implementation and scalability of multimodal learning in Arabic education.